1998
DOI: 10.1002/(sici)1097-4679(199812)54:8<1079::aid-jclp7>3.0.co;2-n
|View full text |Cite
|
Sign up to set email alerts
|

The relationship of psychological-mindedness to adult perceptions of early parental rejection

Abstract: We tested the hypothesis that highly psychologically minded individuals perceive having grown up with rejecting parents. A Psychological Mindedness (PM) Scale, and the Parent-Child Relations Questionnaire II (PCR), were administered to 120 college students. Contrary to prediction, a significant negative correlation was found between PM and perceptions of early maternal rejection. Psychological-mindedness, it was suggested, may be attributable to "good enough mothering" and may be learned through modeling and i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
13
0

Year Published

2002
2002
2016
2016

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 11 publications
1
13
0
Order By: Relevance
“…They found that while psychological mindedness was positively correlated with secure attachment to peers, in contrast to Alvarez et al . 's () research, there was no relationship between psychological mindedness and attachment to either mother or father. Alvarez et al .…”
Section: Introductionmentioning
confidence: 82%
See 1 more Smart Citation
“…They found that while psychological mindedness was positively correlated with secure attachment to peers, in contrast to Alvarez et al . 's () research, there was no relationship between psychological mindedness and attachment to either mother or father. Alvarez et al .…”
Section: Introductionmentioning
confidence: 82%
“…The finding that maternal care is significantly correlated with psychological mindedness supports the previous work of Alvarez et al . (), who found maternal love and lack of demandingness significantly correlated with psychological mindedness. Alvarez et al .…”
Section: Discussionmentioning
confidence: 97%
“…The openness and trust towards counsellors reported by highly psychologically‐minded clients might flow from their reportedly healthy attachment backgrounds (Alvarez, Farber, & Schonbar, 1998). This interpersonal orientation towards others might allow higher PM clients the flexibility to hold heterogeneous expectations about their counsellors.…”
Section: Discussionmentioning
confidence: 99%
“…In terms of interpersonal relations, high PM adults report fewer early maladaptive schemas (Cecero, Beitel, & Prout, 2008), healthier childhood relations to their own parents (Alvarez, Farber, & Schonbar, 1998), and healthier attachment to current peers (Beitel & Cecero, 2003). PM has been associated with a healthy cognitive style, including greater ambiguity tolerance and internal locus of control and less magical thinking (Beitel, Ferrer, & Cecero, 2004).…”
Section: Psychological Mindednessmentioning
confidence: 99%